Comparative approaches to gentrification: Lessons from the rural. Issue 1 (March 2018) - Phillips, Martin; Smith, Darren P
The epistemologies and politics of comparative research are prominently debated within urban studies, with 'comparative urbanism' emerging as a contemporary lexicon of urban studies. The study of urban gentrification has, after some delay, come to engage with these debates, which can be seen to pose a major challenge to the very concept of gentrification. To date, similar debates or developments have not unfolded within the study of rural gentrification. This article seeks to address some of the challenges posed to gentrification studies through an examination of strategies of comparison and how they might be employed within a comparative study of rural gentrification. Drawing on Tilly ( Big structures Large Processes Huge Comparisons . New York: Russell Sage), examples of four 'strategies of comparison' are identified within studies of urban and rural gentrification, before the paper explores how 'geographies of the concept' and 'geographies of the phenomenon' of rural gentrification in the United Kingdom, United States and France may be investigated using Latour's ( Pandora's Hope . London: Harvard University Press) notion of 'circulatory sociologies of translation'. The aim of our comparative discussion is to open up dialogues on the challenges of comparative studies that employ conceptions of gentrification and also to promote reflections of the metrocentricity of recent discussions of comparative research.